2018
DOI: 10.1093/trstmh/try019
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Orientia tsutsugamushi strains circulating in Northeast India

Abstract: KU163366, KY594249, KY594248, KY594251, KU163359, KU163361, KU163363, KU163369, KY594250, KP067915, KU163373, KU163372, KU163370, KU163364, KU163362, KY594247, KY594252, KU163360, KU163365, KU163367, KU163368, KU163371, KX1555826, KY594257, KY594255, KY594256, KX155825, KX155829, KX155827, KX155828, KY594254, KY594253, KY594258, KY583503, KY583499, KY583501, KY583500, KY583502.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…This present study shows that Karp-like and Gilliam-like strains were the most prevailing types. Karp-like strains also predominated in a recent study in the north east of India (Bora et al, 2018). Gilliam-types were the second most common type in our study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…This present study shows that Karp-like and Gilliam-like strains were the most prevailing types. Karp-like strains also predominated in a recent study in the north east of India (Bora et al, 2018). Gilliam-types were the second most common type in our study.…”
Section: Discussionsupporting
confidence: 77%
“…There are more than 20 prototype strains of Orientia tsutsugamushi documented to date (Kelly et al, 2009). From India, there have been a few studies conducted on the genetic diversity of circulating strains (Varghese et al, 2013;Bora et al, 2018). These studies were predominantly from the north, south and extreme north-east of India.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study in north-central Bangladesh, the genetically defined detection rate of O. tsutsugamushi was 17.2% among suspected cases of rickettsial illness. A prevalence of O. tsutsugamushi among febrile patients comparable to our study has been reported in eastern Taiwan (16%) [12], northern Thailand (21%) [13] and northeast India (Assam) (16%, IgM-positive cases) [14]. Accordingly, north-central Bangladesh is also considered to be an endemic area of scrub typhus in South Asia.…”
Section: Discussionsupporting
confidence: 87%
“…A direct method of diagnosis involves isolation and culturing of bacteria in cell lines like L929 (normal fibroblast cell line of the mouse), HeLa (cancer cell line), BHK21 (baby hamster kidney fibroblast cell lines), Vero lineage (isolated from kidney epithelial cells extracted from an African green monkey) and their DNA-based diagnosis using different genetic markers by PCR. Indirect methods of diagnosis include serological assays such as Weil–Felix test, immunofluorescence assay (IFA), enzyme-linked immunosorbent assay (ELISA) and rapid diagnostic assays (Bora et al 2018 ; Lijuan et al 2011 ; Koraluru et al 2015 ; Zhang et al 2011 ).
Fig.
…”
Section: Diagnosis Of Scrub Typhusmentioning
confidence: 99%
“…PCR-based detection methods are highly specific and sensitive for disease diagnosis and can detect bacterial infection even in early stages, unlike serological methods. PCR based detection methods utilize genetic markers such as 56 kDa tsa , GroEL , 16s RNA and 47 kDa HtrA to detect specifically the target organism, i.e., Orientia tsutsugamushi (Bora et al 2018 ; Jiang et al 2004 ; Sonthayanon et al 2009 ; Paris et al 2009 ). The 56 kDa tsa gene is mostly used for the characterization of the O. tsutsugamushi strains.…”
Section: Diagnosis Of Scrub Typhusmentioning
confidence: 99%